Plant remains and associated insects from the Millipede site (13ML361), a burned earthlodge in southwest Iowa. (2nd January 2020) - Green, William; Schirmer, Ronald C.; Billeck, William T.
Abstract : The Millipede site is a Nebraska variant (Central Plains tradition) lodge dating to ca. AD 1300. The structure had burned, preserving a rich array of plant remains and insects. Elm was the principal wood used in lodge construction and hophornbeam (ironwood) was also heavily employed. Maize (mostly 10-row) was plentiful, and common beans also were present. Over 3, 600 goosefoot ( Chenopodium cf. berlandieri ) seeds were recovered, most of which derive from a domesticated variety. Other abundant native domesticated plants included sumpweed and tobacco. Charred insect larvae, mostly darkling beetles (false wireworms), were associated with food remains in the bottom of an open storage pit and on the lodge floor. We conclude that the lodge's residents vacated and intentionally burned the structure. Insect infestation may have contributed to the residents' decision to burn the lodge, but burning also might have formed part of a closing ritual associated with decommissioning the dwelling.